Chicken Embryos as a Potential New Model for Early Onset Type I Diabetes. (13th July 2014) - Shi, Liheng; Ko, Michael L.; Huang, Cathy Chia-Yu; Park, So-Young; Hong, Min-Pyo; Wu, Chaodong; Ko, Gladys Y.-P.
Abstract : Diabetic retinopathy (DR) is the leading cause of blindness among the American working population. The purpose of this study is to establish a new diabetic animal model using a cone-dominant avian species to address the distorted color vision and altered cone pathway responses in prediabetic and early diabetic patients. Chicken embryos were injected with either streptozotocin (STZ), high concentration of glucose (high-glucose), or vehicle at embryonic day 11. Cataracts occurred in varying degrees in both STZ- and high glucose-induced diabetic chick embryos at E18. Streptozotocin-diabetic chicken embryos had decreased levels of blood insulin, glucose transporter 4 (Glut4), and phosphorylated protein kinase B (pAKT). In STZ-injected E20 embryos, the ERG amplitudes of both a- and b-waves were significantly decreased, the implicit time of the a-wave was delayed, while that of the b-wave was significantly increased. Photoreceptors cultured from STZ-injected E18 embryos had a significant decrease in L-type voltage-gated calcium channel (L-VGCC) currents, which was reflected in the decreased level of L-VGCC α 1D subunit in the STZ-diabetic retinas. Through these independent lines of evidence, STZ-injection was able to induce pathological conditions in the chicken embryonic retina, and it is promising to use chickens as a potential new animal model for type I diabetes.